A novel strategy to increase separated electron–hole dipoles in commercial Si based solar panel to assist photovoltaic effect. (3rd January 2018) - Feng, Yefeng; He, Cheng-En; Xu, Zhichao; Hu, Jianbing; Peng, Cheng
Abstract: Interface induced polarization has been found to have a significant impact on dielectric properties of 2-2 type polymer composites bearing Si based semi-conducting ceramic sheets. Inherent overall polarity of polymer layers in 2-2 composites has been verified to be closely connected with interface effect and achieved permittivity in composites. In present work, conducting performances of monocrystalline Si sheets coated by varied high polarity material layers were deeply researched. The positive results inspired us to propose a novel strategy to improve separated electron–hole dipoles in commercial Si based solar cell panel for assisting photovoltaic effect, based on strong interface induced polarization. Conducting features of solar panels coated by two different high polarity polymer layers were detected to be greatly elevated compared with solar panel standalone, thanks to interface induced polarization between panel and polymer. Polymer coating with higher polarity would lead to more separated electron–hole dipole pairs in solar panel contributing to higher conductivity of panel. Valid synergy of interface effect and photovoltaic effect was based on their unidirectional traits of electron transfer. Dielectric properties of solar panels in composites further confirmed that strategy. This work might provide a facile route to prepare promising Si based solar panels with higher photoelectric conversion efficiency by enhancing interface induced polarization between panel and polymer coating.